2015
DOI: 10.1016/j.tvjl.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial collagen deposition and inflammatory cell infiltration in cats with pre-clinical hypertrophic cardiomyopathy

Abstract: The histological features of feline hypertrophic cardiomyopathy (HCM) have been well documented, but there are no reports describing the histological features in mild pre-clinical disease, since cats are rarely screened for the disease in the early stages before clinical signs are apparent. Histological changes at the early stage of the disease in pre-clinical cats could contribute to an improved understanding of disease aetiology or progression. The aim of this study was to evaluate the histological features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 44 publications
4
33
0
Order By: Relevance
“…Similar to our study, in HCM it has been shown that serum levels of PICP are elevated even in mutation carriers without LV hypertrophy, supporting a profibrotic state preceding development of overt cardiomyopathy . Moreover, a histologic study in cats with preclinical HCM showed an increase in myocardial collagen deposition . Furthermore, studies in murine models of HCM have shown upregulation of several extracellular matrix proteins (CTGF [connective tissue growth factor] and POSTN [periostin]) in the very early stage of the disease (prehypertrophic stage, with normal histologic findings) …”
Section: Discussionsupporting
confidence: 88%
“…Similar to our study, in HCM it has been shown that serum levels of PICP are elevated even in mutation carriers without LV hypertrophy, supporting a profibrotic state preceding development of overt cardiomyopathy . Moreover, a histologic study in cats with preclinical HCM showed an increase in myocardial collagen deposition . Furthermore, studies in murine models of HCM have shown upregulation of several extracellular matrix proteins (CTGF [connective tissue growth factor] and POSTN [periostin]) in the very early stage of the disease (prehypertrophic stage, with normal histologic findings) …”
Section: Discussionsupporting
confidence: 88%
“…Despite several anatomopathological studies on feline HCM (Liu et al, 1975(Liu et al, , 1981(Liu et al, , 1993Tilley et al, 1977;Liu and Tilley, 1980;Van Vleet et al, 1980;Van Vleet and Ferrans, 1986;Fox, 2003;Cesta et al, 2005;Kershaw et al, 2012;Khor et al, 2014), the quantitative parameters which allow the characterization of this myocardial disease in veterinary pathology are limited. Similarly to the standardized echocardiographic parameters previously established for diagnosis and classification of feline HCM (Migliorini, 2012), the present study aims to propose an original, complete and repeatable quantitative anatomopathological evaluation of gross and histopathological features of this myocardial disease.…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative evaluation of myocardial fibrosis has already been described for feline HCM (Kershaw et al, 2012;Khor et al, 2014), but without evaluation of the repeatability of the measurement technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations